2018
DOI: 10.1089/jamp.2017.1378
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Doripenem-Loaded Microparticles for Pulmonary Delivery

Abstract: Doripenem-loaded microparticles, produced using a combination of ionotropic gelation and spray-drying methods, are suitable for pulmonary drug delivery based on their particles size, zeta potential, cytotoxicity and high production yield. To our knowledge, this is the first study that microparticles containing doripenem were produced and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The GA-crosslinked MS were rinsed thoroughly with distilled water, and further treated with 4 wt% glycine solution to react with the aldehyde groups in the residual GA [ 45 ]; thus, the potential toxicity was greatly minimized. With regard to the appropriate concentrations of MS in the cytotoxicity studies, most researchers performed the cytotoxicity analysis at a concentration of 10 or 20 mg/mL of the MS [ [46] , [47] , [48] , [49] ]. A previous report by Campos et al showed that when increased the concentrations of GA-crosslinked chitosan–PVA microparticles (CCPMS) to 10.0% (v/v), there was no significant difference in the cell viability compared to the 2.0% (v/v) MS [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GA-crosslinked MS were rinsed thoroughly with distilled water, and further treated with 4 wt% glycine solution to react with the aldehyde groups in the residual GA [ 45 ]; thus, the potential toxicity was greatly minimized. With regard to the appropriate concentrations of MS in the cytotoxicity studies, most researchers performed the cytotoxicity analysis at a concentration of 10 or 20 mg/mL of the MS [ [46] , [47] , [48] , [49] ]. A previous report by Campos et al showed that when increased the concentrations of GA-crosslinked chitosan–PVA microparticles (CCPMS) to 10.0% (v/v), there was no significant difference in the cell viability compared to the 2.0% (v/v) MS [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a lower respiratory tract infection, the overall hospitalization rate of pneumonia is high [ 21 ]. Pneumonia is usually caused by bacteria and viruses, which is a leading disorder leading to the death of children [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Doripenem, a drug belonging to this class, is widely used in the treatment of pneumonia and, similar to others of its class, has low oral bioavailability and is administered intravenously. Yildiz-Peköz et al [ 46 ] proposed doripenem loading in chitosan microparticles, whose properties were optimized using lactose, trehalose and leucine in different concentrations. The in vitro test results showed that microparticles allowed controlled release considered suitable for drugs administered by the pulmonary route.…”
Section: Polymeric Microparticles In Biological Testsmentioning
confidence: 99%